The Impact of Takraw on Physical Fitness: A Study Correlation of Strength, Agility, and Endurance - Oliver, Regtor; Siregar, Octaviananda; Al Hasan, M Iqbal; Elmahdi, Ody Pratama; Siregar, Nurfadillah; Hardiyanto, Nopi (Jurnal Inovasi Olahraga, 2025)
Introduction: Takraw, a traditional Southeast Asian sport combining elements of volleyball and soccer, has gained recognition for its potential physical fitness benefits. However, limited research exists examining the specific correlations between takraw participation and fundamental fitness components. Purpose of the study: This study investigated the correlational relationships between takraw training participation and three key physical fitness components: muscular strength, agility, and cardiovascular endurance among high school students. Materials and methods: A correlational study design was employed with 84 male students (age 16.2 ± 1.1 years) from SMA Swasta PAB 8 Saentis Percut Sei Tuan, North Sumatra, Indonesia. Participants were divided into takraw players (n=42) and non-players (n=42). Physical fitness assessments included grip strength test (strength), Illinois agility test (agility), and 20-meter shuttle run test (endurance). Data analysis was conducted using SPSS version 27. Results: Significant positive correlations were observed between takraw participation and all fitness components. Takraw players demonstrated superior grip strength (45.2 ± 6.8 kg vs. 38.4 ± 5.9 kg, p<0.001), faster agility performance (14.8 ± 1.2 s vs. 16.9 ± 1.8 s, p<0.001), and better endurance capacity (VO₂max: 52.1 ± 4.6 ml/kg/min vs. 44.3 ± 4.1 ml/kg/min, p<0.001). Conclusions: Takraw training shows strong positive correlations with enhanced physical fitness parameters, particularly in strength, agility, and endurance components. These findings support takraw as an effective modality for comprehensive physical fitness development in adolescents.